2001
DOI: 10.1097/00006842-200107000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Diabetes Complications: A Meta-Analysis

Abstract: These findings demonstrate a significant and consistent association of diabetes complications and depressive symptoms. Prospective, longitudinal studies are needed to identify the pathways that mediate this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
998
12
46

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,558 publications
(1,104 citation statements)
references
References 35 publications
48
998
12
46
Order By: Relevance
“…Increased risk for depression in people with diabetes may also be attributed to lifestyle and health behaviours; for example, a recent longitudinal study from the Canary Islands showed that intake of trans-unsaturated fatty acids, but not of mono-or polyunsaturated fatty acids, was associated with increased levels of depression (Sánchez-Villegas et al, 2011). Depression risk factors that are specific to diabetes include co-morbidity of diabetes-related complications (de Groot et al, 2001), and in particular macrovascular disease (stroke, peripheral artery disease) (Bruce et al, 2006) and microvascular disease including retinopathy ), neuropathy and nephropathy (van Steenbergen-Weijenburg et al, 2011), longer duration of diabetes (Padgett, 1993;, more demanding regimens (Surwit et al, 2005), low levels of daily activities (Wikblad et al, 1991;Pawaskar et al, 2007) and physical activity (Lysy et al, 2008), ), nutrition e.g., low intake of omega-3 fatty acids (Fitten et al, 2008), and perceived burden of diabetes (Polonsky et al, 1995). The majority of these studies, however, were cross-sectional and studied factors associated with depressive symptoms rather than with a diagnosis of major depression.…”
Section: Risk Factors For Developing Depression In People With Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased risk for depression in people with diabetes may also be attributed to lifestyle and health behaviours; for example, a recent longitudinal study from the Canary Islands showed that intake of trans-unsaturated fatty acids, but not of mono-or polyunsaturated fatty acids, was associated with increased levels of depression (Sánchez-Villegas et al, 2011). Depression risk factors that are specific to diabetes include co-morbidity of diabetes-related complications (de Groot et al, 2001), and in particular macrovascular disease (stroke, peripheral artery disease) (Bruce et al, 2006) and microvascular disease including retinopathy ), neuropathy and nephropathy (van Steenbergen-Weijenburg et al, 2011), longer duration of diabetes (Padgett, 1993;, more demanding regimens (Surwit et al, 2005), low levels of daily activities (Wikblad et al, 1991;Pawaskar et al, 2007) and physical activity (Lysy et al, 2008), ), nutrition e.g., low intake of omega-3 fatty acids (Fitten et al, 2008), and perceived burden of diabetes (Polonsky et al, 1995). The majority of these studies, however, were cross-sectional and studied factors associated with depressive symptoms rather than with a diagnosis of major depression.…”
Section: Risk Factors For Developing Depression In People With Diabetesmentioning
confidence: 99%
“…It is therefore not surprising that depression is also associated with an increased number of diabetes-related complications (de Groot et al, 2001), health service utilisation and healthcare costs (Egede et al, 2002) and mortality (Katon, 2011;Ismail et al, 2007). Concerning the latter, people with diabetes and major and minor depression have a 2.3 and 1.67 fold increase in mortality respectively compared to those without depression (Katon et al, 2005).…”
Section: Consequences Of Depression In People With Diabetesmentioning
confidence: 99%
“…3 Depression, an important comorbidity among adults with diabetes, has been associated with poorer disease selfmanagement and greater risk of diabetic complications, including microvascular and macrovascular disease, demen-tia, and early mortality. [4][5][6][7][8] This association is substantial in magnitude; estimates suggest that smoking, poor diet, and inactivity may be increased by 30-100 % and the risk for adverse outcomes including dementia and mortality doubles when diabetes is complicated by depression. [5][6][7] However, depression is often unrecognized among patients with diabetes in primary care settings, and adequate antidepressant treatment is received by less than one-third of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes and major depression are mutual risk factors with diabetic patients more likely to develop major depression with an odds ratio of 2.5 according to one study (Palinkas et al, 2004) and depressed patients being more likely to develop type 2 diabetes with an estimated relative risk of 2.2 according to another study (Eaton et al, 1996). Depression also has a significant impact on the course of diabetes leading to higher rates of hyperglycemia and diabetic complications (de Groot et al, 2001;Lustman and Clouse, 2005).…”
Section: Introductionmentioning
confidence: 99%